SUBVERTING THE GENRE: FEMINIST DIMENSIONS AND NARRATIVE STRATEGY IN THE DETECTIVE FICTION OF P.D. JAMES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This thesis explores feminist dimensions in the detective novels of P.D. James, focusing on An Unsuitable Job for a Woman (1972) and A Taste for Death (1986). By introducing Cordelia Gray as one of the first professional female private detectives, James challenges the patriarchal assumptions of classical detective fiction. Similarly, A Taste for Death highlights female resilience and moral agency within a crime narrative. The research demonstrates that James’s works not only preserve the conventions of the genre but also extend its thematic boundaries by incorporating feminist concerns.